Music Composition Saka Luang | Komposisi Musik Saka Luang - I Putu Agus Dodik Budimahendra; Kadek Suartaya (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The composition of the final project “Saka Luang” is a work that is formed and is classified as an innovative karawitan composition. The formation of the title “Saka Luang” was inspired by the stylist’s inspiration from the building palinggih menjang saluang which can be interpreted, Saka which means pillar or adegan (warna, 1988:252). And Luang means eka or single (Ariana, 2016:49). So “Saka Luang” the stylist interprets as a pillar to focus the mind so that it becomes Luang. This work from the technique departs to Leluangan, the interpretation of ideas and the Leluangan technique is poured into the media sai Gamelan Semar Pagulingan Saih Pitu in order to be able to play patet according to the atmosphere and nuances to be achieved. The creative process used in the creation stage of this work uses the method written by I Wayan Diana Putra mentioned by Senen from the creation stage of I Wayan Beratha who adheres to three processes, namely, Nguping (imitation), Menahin (improvement), and Ngelesin (refining). Keywords: Semar Pagulingan, Leluangan, Saka Luang.